2018
DOI: 10.1111/ffe.12869
|View full text |Cite
|
Sign up to set email alerts
|

Numerical determination of plastic CTOD

Abstract: In previous works, a da/dN versus plastic crack tip opening displacement model was proposed to study fatigue crack growth. The plastic crack tip opening displacement, δp, which quantifies the crack tip plastic deformation, is determined numerically using the finite element method. The predictions are affected by different numerical parameters which must be identified and studied. The main parameters are the crack propagation distance, the distance of measurement points relatively to the crack tip, the size of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 29 publications
0
10
0
Order By: Relevance
“…To talk about numerical models of crack growth and their relation to plastic phenomena in the crack tip environment is to talk about Fernando Antunes. Building on the discrete approach by Pokluda [66], Antunes [67] presents an elasto-plastic numerical model, which provides a different perspective by excluding the contact between the crack flanks, thereby focusing on the relationship between CTOD, plastic phenomena at the crack tip, and crack growth rate. The work [67] presents an elasto-plastic numerical model where On a similar note, Zhang [63] developed a fatigue crack propagation model emphasising the effect of compressive stress, thereby adding another dimension to the understanding of fatigue crack growth under tension-compression loading.…”
Section: Damage Theories Based On Crack Growth Concepts-ctod Plastic ...mentioning
confidence: 99%
See 3 more Smart Citations
“…To talk about numerical models of crack growth and their relation to plastic phenomena in the crack tip environment is to talk about Fernando Antunes. Building on the discrete approach by Pokluda [66], Antunes [67] presents an elasto-plastic numerical model, which provides a different perspective by excluding the contact between the crack flanks, thereby focusing on the relationship between CTOD, plastic phenomena at the crack tip, and crack growth rate. The work [67] presents an elasto-plastic numerical model where On a similar note, Zhang [63] developed a fatigue crack propagation model emphasising the effect of compressive stress, thereby adding another dimension to the understanding of fatigue crack growth under tension-compression loading.…”
Section: Damage Theories Based On Crack Growth Concepts-ctod Plastic ...mentioning
confidence: 99%
“…Building on the discrete approach by Pokluda [66], Antunes [67] presents an elasto-plastic numerical model, which provides a different perspective by excluding the contact between the crack flanks, thereby focusing on the relationship between CTOD, plastic phenomena at the crack tip, and crack growth rate. The work [67] presents an elasto-plastic numerical model where On a similar note, Zhang [63] developed a fatigue crack propagation model emphasising the effect of compressive stress, thereby adding another dimension to the understanding of fatigue crack growth under tension-compression loading. The stress near the crack tip, the displacement, and the size of the plastic zone were obtained from a kinematically hardened material.…”
Section: Damage Theories Based On Crack Growth Concepts-ctod Plastic ...mentioning
confidence: 99%
See 2 more Smart Citations
“…It was observed that the plastic-induced crack closure has a substantial influence on the delay effect of fatigue load. Antunes [7] used the finite element method to determine the plastic CTOD values under the action of different crack increments, including different crack tip mesh sizes and different loading cycles in the numerical method. In recent years, the research based on 3D-DIC of CTOD has advanced rapidly with the development of digital image correlation technology.…”
Section: Introductionmentioning
confidence: 99%